Application of advanced technologies for CO2 capture from industrial sources - Romano, Matteo C. (2014)
The great majority of the research on CO2 capture worldwide is today devoted to the integration of new technologies in power plants, which are responsible for about 80% of the worldwide CO2 emission from large stationary sources. The remaining 20% are emitted from industrial sources, mainly cement production plants (~7% of the total emission), refineries (~6%) and iron and steel industry (~5%). Despite their lower overall contribution, the CO2 concentration in flue gas and the average emission per source can be higher than in power plants. Therefore, application of CO2 capture processes on these sources can be more effective and can lead to competitive cost of the CO2 avoided with respect to power plants. Furthermore, industrial CO2 capture could be an important early-opportunity application, or a facilitate demonstration of capture technology at a relative small scale or in a side stream. This paper results from a collaborative activity carried out within the Joint Programme on Carbon Capture and Storage of the European Energy Research Alliance (EERA CCS-JP) and aims at investigating the potentiality of new CO2 technologies in the application on the major industrial emitters.